Anti-ulcer Effect of Gastroretentive Drug Delivery System of Alginate Beads Containing Turmeric Extract Solid Dispersion - Bangun, Hakim; Arianto, Anayanti; Rehngenana, Elfina (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Treatment of gastric ulcer using turmeric extract is less effective because curcumin has low solubility and degraded in alkaline intestinal pH. Therefore, it is necessary to convert turmeric extract into turmeric solid dispersion to increase the dissolution of curcumin and the preparation is made in gastroretentive drug delivery system to improve the absorption of curcumin in the stomach. AIM: The aim of the study was to determine the anti-ulcer effect of gastroretentive drug delivery system of alginate beads containing turmeric extract solid dispersion compared to alginate beads containing turmeric extract (without solid dispersion) and negative control. METHODS: Turmeric powder was macerated with 96% ethanol for 8 days. The macerate was evaporated with a rotary evaporator at 50°C to obtain a concentrated extract. Turmeric extract solid dispersion was prepared by the solvent method using polyvinylpyrrolidone as a carrier. The turmeric extract solid dispersion was encapsulated with alginate gel by gelation method. The antiulcer test was performed on rats with gastric ulcer that induced by 0.6 N HCl solution. The ulcer healing was observed macroscopically and microscopically (histopathology). RESULTS: The results of observation on the treatment of rats gastric ulcer that induced by 0.6 N HCl showed the gastroretentive drug delivery system of alginate beads containing turmeric extract solid dispersion effective in healing the gastric ulcer compared to negative control. The effectiveness was statistically significantly different (p < 0.05). Alginate beads containing turmeric solid dispersion were slightly more effective than alginate beads containing turmeric extract, but the effectiveness was not statistically significant (p > 0.05). CONCLUSION: Alginate beads containing turmeric extract solid dispersion were effective in treatment of gastric ulcer in rats.